2021
DOI: 10.1101/2021.12.23.474055
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Establishment of a stable SARS-CoV-2 replicon system for application in high-throughput screening

Abstract: Experiments with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are limited by the need for biosafety level 3 (BSL3) conditions. A SARS-CoV-2 replicon system rather than an in vitro infection system is suitable for antiviral screening since it can be handled under BSL2 conditions and does not produce infectious particles. However, the reported replicon systems are cumbersome because of the need for transient transfection in each assay. In this study, we constructed a bacterial artificial chromoso… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Spontaneous mutations in nsp4 and nsp10 were identified in almost all replicon RNA populations isolated for cells stabling maintaining the replicons, which could be suggestive of adaptive mutations that allowed for non-cytopathic replication in BHK-21 cells (37). Furthermore, a study reporting the isolation of Vero E6 populations stably maintaining a minimal replicon did not include the nsp1 mutations in the replicon genome, although the sequences of the stably maintained replicons were not determined (59).…”
Section: Resultsmentioning
confidence: 99%
“…Spontaneous mutations in nsp4 and nsp10 were identified in almost all replicon RNA populations isolated for cells stabling maintaining the replicons, which could be suggestive of adaptive mutations that allowed for non-cytopathic replication in BHK-21 cells (37). Furthermore, a study reporting the isolation of Vero E6 populations stably maintaining a minimal replicon did not include the nsp1 mutations in the replicon genome, although the sequences of the stably maintained replicons were not determined (59).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Ricardo-Lax et al failed to select a stable cell line containing the YAC-derived SARS-CoV-2 replicon with the Nsp1 K164A/H165A mutations in both Huh-7.5 and BHK-21 cells. In contrast, Tanaka et al successfully obtained a stable VeroE6 cell line that harbors the BAC plasmid-derived SARS-CoV-2 replicon without introducing any mutations into the SARS-CoV-2 genome ( Tanaka et al, 2022 ), arguing different cell backgrounds and multiple adaptive mutations may be necessary. These two stable SARS-CoV-2 replicons have been proven effective in screening inhibitors against SARS-CoV-2 replication.…”
Section: Bsl2-adapted Sars-cov-2 Reverse Genetic Systemsmentioning
confidence: 99%
“…The first reverse genetics system for coronavirus was successfully constructed with a targeted RNA recombination strategy. 21 , 22 , 23 Homologous RNA recombination is common in regions with high sequence similarity during viral RNA replication. 24 Lai et al first reported that RNA recombination mediates the fusion of RNA of different mouse hepatitis virus (MHV) strains during genome replication.…”
Section: Reverse Genetics Systems Based On Rna Recombinationmentioning
confidence: 99%
“…The first reverse genetics system for coronavirus was successfully constructed with a targeted RNA recombination strategy 21–23 . Homologous RNA recombination is common in regions with high sequence similarity during viral RNA replication 24 .…”
Section: Reverse Genetics Systems Based On Rna Recombinationmentioning
confidence: 99%